Needs Analysis for Game-Based Learning Integration: Developing Blooket Media for Teaching Matter and Its Changes in Junior High School - Putri Rahma; M. Hidayat; Erlida Amnie (Journal of Advances in Physics Education, 2026)
Background: Junior high school students often struggle with the abstract concepts of physics, particularly in the topic of Matter and Its Changes. This study aims to analyze the need for integrating Blooket, a game-based learning platform, to address these learning difficulties. Methods: A mixed-methods approach was employed, combining semi-structured interviews with two science teachers and a needs assessment questionnaire administered to 26 eighth-grade students at Adhyaksa 1 Junior High School in Jambi. Qualitative data were analyzed thematically, while quantitative data were processed descriptively. Results: The findings indicate that 88.5% of students experience difficulties in learning physics, with 61.5% identifying Matter and Its Changes as the most challenging topic. Key contributing factors included abstract material (30.8%), unclear explanations (38.5%), and lack of real-life examples (26.9%). Conversely, student interest in game-based learning was very high: 92.3% expressed interest in using Blooket, and 57.7% believed educational games enhance learning activity. Teacher support and high digital device accessibility (96.2%) further support its feasibility. Conclusion: There is a strong need for interactive, game-based media like Blooket to bridge the gap between students' learning difficulties and their high interest in engaging methods. This media is proposed as a potential solution to visualize abstract concepts and increase motivation in physics education.